2007
DOI: 10.1002/ca.20457
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion of ascending lumbar and iliolumbar veins in anterior spinal surgery: An anatomical study

Abstract: To expose the disc between the 4th and 5th lumbar vertebrae in anterior spinal surgery, left to right retraction of inferior vena cava and aorta is required. This manoeuvre can be complicated by venous haemorrhage that, in most cases, is due to avulsion of the left ascending lumbar vein (ALV) or the left iliolumbar vein (ILV). We dissected 23 embalmed cadavers to assess the factors that contribute to the risk of tearing these two veins during retraction. We describe a triangular region that should help surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
2
15
0
2
Order By: Relevance
“…One previous study suggests that the only significant difference between right and left ILVs is that the distance of the ILV to the IVC confluence on the left tends to be farther away from the IVC than those on the right (Kiray et al, 2004;Hamid et al, 2007). A separate study has shown no significant difference between the two sides (Sivakumar et al, 2007). Our study confirms the former.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…One previous study suggests that the only significant difference between right and left ILVs is that the distance of the ILV to the IVC confluence on the left tends to be farther away from the IVC than those on the right (Kiray et al, 2004;Hamid et al, 2007). A separate study has shown no significant difference between the two sides (Sivakumar et al, 2007). Our study confirms the former.…”
Section: Discussionsupporting
confidence: 93%
“…They felt that the male venous structures may be more susceptible to avulsion upon retraction to the right side as four of five avulsions that occurred in their study were in male cadavers, but they also admitted that this was too small of a sample size to make any firm conclusions (Sivakumar et al, 2007). All other differences in their comparison of male and female cadavers were not statistically significant.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations